2015
DOI: 10.1093/heapol/czu062
|View full text |Cite
|
Sign up to set email alerts
|

Quality of inpatient care in public and private hospitals in Sri Lanka

Abstract: For a range of indicators where comparisons were possible, quality of inpatient clinical care in Sri Lanka was comparable to levels reported from upper-middle income Asian countries, and often approaches that in developed countries, although the findings cannot be generalized. Quality in the public sector is better than in the private sector in many areas, despite spending being substantially less. Quality in public hospitals is resource constrained, and needs greater government investment for improvement, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 38 publications
1
47
0
2
Order By: Relevance
“…Nuwara Eliya is historically underdeveloped [30, 51, 52]. It continues to not be a priority for national investment in health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuwara Eliya is historically underdeveloped [30, 51, 52]. It continues to not be a priority for national investment in health.…”
Section: Discussionmentioning
confidence: 99%
“…The Vanni served as both a fictive homeland and administrative center for the LTTE, and proved to have a comparatively stable boundary. Although the LTTE undertook state-building effort in theVanni, the GoSL continued to supply moderate health and educational resources to the embattled districts [30]. The remaining district in the Northern Province, Jaffna, is situated in a strategically important peninsula.…”
Section: Introductionmentioning
confidence: 99%
“…Dubious practices are also common, such as the transfer of patients at high risk from private facilities to public sector hospitals 25. A notable exception is Sri Lanka, where high technical quality in inpatient and outpatient primary care has been observed in both public and private sectors 2627…”
Section: Access To Healthcarementioning
confidence: 99%
“…Although higher financial backing and international know-how should translate into better quality of private and foreign hospitals, Rannan-Eliya et al [24] found that Sri Lankan public hospitals performed better in overall medical effectiveness, but worse for resource-intensive dimensions such as interpersonal skills and turnaround time. In contrast, Indian patients felt more assured with the reliable personnel and modern equipment in private hospitals.…”
Section: Hospital Choice Factors In Developing Economiesmentioning
confidence: 99%